PEMANFANTAN INTERNET SEABAGAI MEDIA AKSES INFORMASI DALAM MENUNJANG KEGIATAN PEMBELAJARAN PAI SISWA SMP MUHAMMADIYAH 06 DAU MALANG - Moh Kandarisman; Azhar Haq; Dian Mohammad Hakim (VICRATINA, 2021)
The use of the internet which is used as a medium for accessing information in supporting PAI learning activities is not optimal. Learning by using the internet should have been able to be applied to support PAI learning activities and PAI information in the classroom, but thSere is still misuse. The purpose of this study is (1) to describe the application of the use of the internet as a medium for accessing information in supporting PAI learning activities for students of SMP Muhammadiyah Dau Malang. (2) Describe the problems of using the internet as a medium of access to information in supporting PAI learning activities for students of SMP Muhammadiyah Dau Malang. (3) Knowing the results achieved from the use of the internet as a medium of access to information in supporting PAI learning activities for students of SMP Muhammadiyah Dau Malang. The results of this study are (1) the use of the internet as a medium of access to information in supporting PAI learning for students of SMP Muhammadiyah 06 Dau Malang. (2) The problem of using the internet as a medium for accessing information in supporting PAI learning for students at SMP Muhammadiyah 06 Dau Malang is the economic factor. (3) The use of the internet in PAI learning at SMP Muhammadiyah 06 Dau Malang is applied as access to information in supporting PAI learning activities, namely a learning program that combines information and communication technology or web based with face-to-face meetings